The role of municipal ownership for urban net-zero path creation - Sugar, Katherine (Frontiers in Sustainable Energy Policy, 2024)
Particularly within recent years, the rising number of city actors worldwide declaring climate emergencies and pledging commitments to carbon neutrality has sparked a spatial turn in broader sustainable transition thinking, noting the importance of the local level for governing sustainable transitions. Using a Geographical Political Economy approach, this paper critically engages with path creation theory and sustainable transitions literature to explore the potential of urban net-zero carbon transitions in a multi-scalar governance framework. The main argument is that municipal ownership across sectors has a fundamental role in sustainable transitions at the city level. This paper makes a distinct conceptual contribution to sustainable transitions literature by drawing on path creation theory to illustrate how municipal ownership is a central tenet of path creation by bringing together local actors and enabling political capacity and agency to control and strategize integrated sustainable urban pathways. Using the transport and energy sectors in Nottingham in the UK, it applies the Path Creation Framework in an urban setting to illustrate that municipal ownership stimulates a positive path creation through three main arguments. First, municipal ownership enables a positive embeddedness and historical legacy in the provision of sustainable urban energy and transport services; second, it facilitates the establishment of skills and expertise that positively reinforces urban political capacity for the pursuit of urban sustainability; and third, it stimulates the creation of innovative urban projects for sustainable and equitable pathways.